Pengembangan Ekonomi Masyarakat Asli Berbasis Komoditi Kayu Putih di Kawasan Taman Nasional - sebestina siman; Hendricus Lembang (Faculty Of Economics and Business, Musamus University, 2022)
The purpose of this study is to determine determine the cluster of local community comodity development areas, namely eucalyptus oil, development policies and the constraints faced by indigenous people eucalyptus oil business actors. The type of research used is a desciptive qualitative approach. Tehniques of obtaining data are observation, interview and library research. The results of this study indicate that eucalyptus oil has prospect for indigenous people in 4 villages, in the Wasur National Park Area. Wasur Village, Rawa Biru Village, Yangandur Village and Sota Village as cluster of eucalyptus oil business oil development, the obstacles faced are the work spirit and mindset that is not yet oriented to a wider market, the long distance from the source of the leaves to the place of processing, the level of productivity labor force is still low, seasonal dependence, management and competitiveness still low. So that the management development policies adopted are partnership policy, creating of a healty business atmosphere policy and increasing competitivness policy. Keywords: local economy, comodity, eucalyptus oil, policy